Risk Analysis of the Impact of Pandemic COVID-19 on the Health and Economy of Fishery Households in Kedung Cowek Village, Bulak, Surabaya - Mohammad Hadiyan Ghafara; Widi Agoes Pratikto; Silvianita Silvianita (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2022)
Since the COVID-19 pandemic hit Indonesia, many fishery households on Indonesia's coast have been affected. Therefore, an analysis of the impact of the COVID-19 pandemic was carried out on the health and economy of fisheries households in the coastal areas of Kenjeran Beach, especially in Kedung Cowek Village, Bulak, Surabaya. The Fault Tree Analysis (FTA) method is used to find the probability of decreasing fisheries household welfare and the Event Tree Analysis (ETA) to find the level of risk for each factor causing the decline in the welfare of fishery households. The analysis result shows that 21 factors cause household welfare in Kenjeran Beach to decline, grouped into two intermediate events: decreasing fisheries household income and decreasing fishery household health. The probability of fishery household welfare decreases by 0.0171212. Decreasing welfare of fisheries households has a risk that fisheries household income will not experience a decrease in income, and there is no spread of COVID-19, with a risk probability of 0.0052 and having a medium risk index level. Based on this, stakeholders in the income and health of fisheries households such as the government, analytical institutions, and households have a role in mitigating the impact of COVID-19.